ITGB1-DT Facilitates Lung Adenocarcinoma Progression via Forming a Positive Feedback Loop With ITGB1/Wnt/β-Catenin/MYC - Chang, Ruimin; Xiao, Xiaoxiong; Fu, Yao; Zhang, Chunfang; Zhu, Xiaoyan; Gao, Yang (Frontiers in Cell and Developmental Biology, 2021)
Lung adenocarcinoma (LUAD) is the main histological type of lung cancer, which is the leading cause of cancer-related deaths. Long noncoding RNAs (lncRNAs) were recently revealed to be involved in various cancers. However, the clinical relevance and potential biological roles of most lncRNAs in LUAD remain unclear. Here, we identified a prognosis-related lncRNA ITGB1-DT in LUAD. ITGB1-DT was upregulated in LUAD and high expression of ITGB1-DT was correlated with advanced clinical stages and poor overall survival and disease-free survival. Enhanced expression of ITGB1-DT facilitated LUAD cellular proliferation, migration, and invasion, and also lung metastasis in vivo. Knockdown of ITGB1-DT repressed LUAD cellular proliferation, migration, and invasion. ITGB1-DT interacted with EZH2, repressed the binding of EZH2 to ITGB1 promoter, reduced H3K27me3 levels at ITGB1 promoter region, and therefore activated ITGB1 expression. Through upregulating ITGB1, ITGB1-DT activated Wnt/β-catenin pathway and its downstream target MYC in LUAD. The expressions of ITGB1-DT, ITGB1, and MYC were positively correlated with each other in LUAD tissues. Intriguingly, ITGB1-DT was found as a transcriptional target of MYC. MYC directly transcriptionally activated ITGB1-DT expression. Thus, ITGB1-DT formed a positive feedback loop with ITGB1/Wnt/β-catenin/MYC. The oncogenic roles of ITGB1-DT were reversed by depletion of ITGB1 or inhibition of Wnt/β-catenin pathway. In summary, these findings revealed ITGB1-DT as a prognosis-related and oncogenic lncRNA in LUAD via activating the ITGB1-DT/ITGB1/Wnt/β-catenin/MYC positive feedback loop. These results implicated ITGB1-DT as a potential prognostic biomarker and therapeutic target for LUAD.